2019
DOI: 10.1016/j.mito.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free mitochondrial DNA in progressive multiple sclerosis

Abstract: Recent studies have linked cell-free mitochondrial DNA (ccf-mtDNA) to neurodegeneration in both Alzheimer's and Parkinson's disease, raising the possibility that the same phenomenon could be seen in other diseases which manifest a neurodegenerative component. Here, we assessed the role of circulating cell-free mitochondrial DNA (ccf-mtDNA) in end-stage progressive multiple sclerosis (PMS), where neurodegeneration is evident, contrasting both ventricular cerebral spinal fluid ccf-mtDNA abundance and integrity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 44 publications
1
36
1
1
Order By: Relevance
“…ccf-mtDNA copy number was calculated as an absolute measurement of MTND1 (minor deletion arc mitochondrial gene) and derived from a triplicated standard curve and is expressed as copies per 1 μl of CSF. As in previous work [19,33], samples with > 1 B2M copies per microliter (indicating nuclear DNA contamination) were removed from further analysis (0 months: PD patients = 81, 28% and controls = 37, 28%, and 36 months: PD patients =74, 30% and controls = 27, 23%), leaving a final cohort of 423 samples at 0 months (291 PD patients and 132 controls) and 263 samples at 36 months (176 PD patients and 87 controls).…”
Section: Ppmi Csf Sample Cohort Ppmi Cohort Characteristicsmentioning
confidence: 59%
See 2 more Smart Citations
“…ccf-mtDNA copy number was calculated as an absolute measurement of MTND1 (minor deletion arc mitochondrial gene) and derived from a triplicated standard curve and is expressed as copies per 1 μl of CSF. As in previous work [19,33], samples with > 1 B2M copies per microliter (indicating nuclear DNA contamination) were removed from further analysis (0 months: PD patients = 81, 28% and controls = 37, 28%, and 36 months: PD patients =74, 30% and controls = 27, 23%), leaving a final cohort of 423 samples at 0 months (291 PD patients and 132 controls) and 263 samples at 36 months (176 PD patients and 87 controls).…”
Section: Ppmi Csf Sample Cohort Ppmi Cohort Characteristicsmentioning
confidence: 59%
“…Ccf-mtDNA quantification ccf-mtDNA was quantified using established methods [19,33]. ccf-mtDNA copy number was calculated as an absolute measurement of MTND1 (minor deletion arc mitochondrial gene) and derived from a triplicated standard curve and is expressed as copies per 1 μl of CSF.…”
Section: Ppmi Csf Sample Cohort Ppmi Cohort Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have associated decreased levels of circulating cellfree mtDNA in the cerebrospinal fluid (CSF) from patients afflicted by Alzheimer's and Parkinson's disease with neurodegeneration (Podlesniy et al, 2013;Pyle et al, 2015). Similarly, reduced concentrations of circulating mtDNA were detected in the CSF of end-stage progressive MS with evidence of neurodegeneration (Lowes et al, 2019). Conversely, a significantly higher level of CSF cell-free mtDNA was found in relapsing-remitting (RR) MS patients, as well as an inverse correlation between circulating mtDNA concentration and time since disease onset, suggesting that free mtDNA level may reflect early, active inflammatory activity (Varhaug et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering observations reported that high mobility group box protein 1 (HMGB1, a non-histone DNA-binding protein acting as transcriptional regulator and as nucleosome stabilizer) plays a role either in MS or in experimental autoimmune encephalomyelitis (Andersson et al, 2008). Recent studies have also suggested putative associations between DAMPs arising from mitochondrial (mt) components, particularly circulating cell-free mtDNA, and MS progression (Leurs et al, 2018;Lowes et al, 2019). Such DAMPs could induce the production of cytokines and other pro-inflammatory mediators that trigger and maintain the inflammatory environment, leading to a dysregulated and imbalanced cytokine network, well described in MS patients (Kallaur et al, 2017;Khaibullin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%